2021
DOI: 10.3390/ijerph182111643
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of Socio-Labor Integration in Chile: Migrating Colombian Women’s Experiences

Abstract: The objective of the article is to understand Afro-Colombian women’s emotional experiences of the migratory process, and their labor insertion in Chilean territory. The Antofagasta region is one of the doors that connects Chile with its neighbors; at the same time, it is a national territory that is linked to important economic and human movements due to its mining activity. In the analysis of the data collected through of group and individual interviews conducted in the city of Antofagasta, we found experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Consequently, the condition of women depends to a large extent on the male figure, thus increasing their vulnerability. It was observed that the female group did not report the abuses for fear of possible reprisals(Silva & Castillo, 2021).The findings of this study suggest that the barriers to accessing the health system could be the result of the alignment of cultural experiences, marginalization and discrimination, which affect the health needs of this group and consolidate the inequities of the system. A lack of financial resources is another indicator of SDH, which prevents this study's participants from buying the medication they need or getting public transport to a healthcare centre, due to distance.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Consequently, the condition of women depends to a large extent on the male figure, thus increasing their vulnerability. It was observed that the female group did not report the abuses for fear of possible reprisals(Silva & Castillo, 2021).The findings of this study suggest that the barriers to accessing the health system could be the result of the alignment of cultural experiences, marginalization and discrimination, which affect the health needs of this group and consolidate the inequities of the system. A lack of financial resources is another indicator of SDH, which prevents this study's participants from buying the medication they need or getting public transport to a healthcare centre, due to distance.…”
mentioning
confidence: 70%
“…Consequently, the condition of women depends to a large extent on the male figure, thus increasing their vulnerability. It was observed that the female group did not report the abuses for fear of possible reprisals (Silva & Castillo, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, gender discrimination has long existed in the labor market, and female migrant workers are a vulnerable group of migrant workers [56,57]. Engaging in selfemployment helps female migrant workers get rid of heavy manual labor.…”
Section: Self-employment Healthmentioning
confidence: 99%